Interview: Core European values under threat - Weiss, Stefani (Gütersloh, 2017)
"Hungary and Poland are violating core principles of law in the EU and are neglecting the rulings of the European Court of Justice. Former Vice President of the European Commission, Viviane Reding, is giving us her opinion on what the EU can and must do to reinforce the respect for the rule of law which forms the very foundation of the EU."